MEMBANDINGKAN JUMLAH LEUKOSIT DAN NILAI LAJU ENDAP DARAH PASIEN TUBERKULOSIS PARU SEBELUM DAN SETELAH PENGOBATAN - Chairani, Chairani; Novita, Eka (IAIN Batusangkar, 2018)
Tuberculosis is a serious health problem that should be concerned. According statistic of The World Health Organization (WHO) show there are 1,7 million deaths due to tuberculosis. Indonesia inclue one of 3 highest incidence of tuberculosis cases in the world. This study aimed to determine the number of leucocytes and erithrocyte sediment rate (ESR) with pulmonary tuberculosis before and after administration of the anti-tuberculosis drugs (OAT). This study used description crosssectional research design. Observations were carried out in patients with tuberculosis who received therapy for 6 months OAT agains leucocytes and ESR before and after treatment. Subjects were new case of pulmonary tuberculosis with acid fast bacilli (BTA) positive and BTA negative Rontgen positive in Dharmasraya district. Materials such examination whole blood samples with EDTA anticoagulant. The result subject are 30 people. Examination of leucocytes and ESR performed before and after administration of the OAT. Result of data analysis showed that changesin the number of leucocytes significance value p=0,000 (< 0,05) and ESR significance value p=0,000 (< 0,05). This suggest that there are significant differences in the number of the leucocytes and ESR before and after administration of the antituberculosis drugs.